Structural aspects of MOF-based energy materials research at Diamond - Allan, David R.; Blake, Alexander J.; Schröder, Martin; Tang, Chiu C.; Yang, Sihai (The Royal Society, 2015)
Large-scale central facilities such as Diamond Light Source fulfil an increasingly pivotal role in many large-scale scientific research programmes. We illustrate these developments by reference to energy-centred projects at the University of Nottingham, the progress of which depends crucially on access to these facilities. Continuing access to beamtime has now become a major priority for those who direct such programmes